Perceptions towards Working Women of the Organisation:An Exploratory Study in Yemen - Jarhum, Rasha Rashid (2007)
This research paper explores the perceptions and stereotyping associated with working women in Yemen, noting how they work in concert to promote and maintain particular constructions of masculinity and femininity. Conventional stereotyping of roles of men and women outside the workplace, as breadwinner and caregiver/housewife respectively, influence perceptions within the workplace, affecting both men and women, generally to the detriment of women, and leading to gendered processes and their asymmetrical effects. Chapter one offers an introduction to the research, research questions, statement of objectives, and then concludes with an overview about the status of working women. Chapter two reviews the methodology and research designed followed. Chapter three covers the related literature such as working women and Islam, the gender concept, the traditional gender paradigm in the MENA (Middle East and North Africa) region, organisational behaviour, and perceptions and stereotyping. Chapter four includes the analysis and interpretation of data, ending with chapter five which offers the conclusion and recommendations.